Commitment to organization versus commitment to profession: conflict or compatibility? - Nik Mutasim Ab. Rahman; Mohd. Hizam Hanafiah (Penerbit Universiti Kebangsaan Malaysia, 2002)
There has been an interesting debate in organizational behavior literature on whether conflict or compatibility characterizes the relationship between employees’ commitment to the organization and their commitment to the profession. To address this issue, a survey was conducted on a sample of research scientists in research institutions in the Klang Valley of Malaysia. Based on the analysis involving a sample size of 545 research scientists, the findings confirmed the assumption that there is no conflict between these concepts. Significant relationship exist between commitment to profession and the affective, continuance, and normative dimensions of commitment to the organization (coefficients of 0.43, 0.15, and 0.52 respectively). In other words, the results suggest that commitment to organization is compatible with commitment to profession. The outcome of the survey further suggests the relevance of assessing the relationship in the context of multidimensionality of, not only organizational commitment, but also of commitment to profession